Influence of Facilities, Promotion, Product and Location Islamic Banking on Decision Non Muslim Customers Patronizing at BRIS Case Study in BRI Syariah - Firza Aulia Viranti; Adhitya Ginanjar (Tauhidinomics: Journal of Islamic Banking and Economics, 2015)
The purpose of this study was to see how big the influence of facilities, promotion, product and location Islamic Banking affect the Non Muslim customers to patronize at BRIS. The data used in this research was the primary data that obtained from the division of a detailed questionnaire to the non muslim customers Islamic Bank on Jl. Gatot Subroto no.38 Jamsostek Tower, South- Jakarta. Sampling method used by reasearcher was a purposive sampling where this was a study of the phenomenon or specific populations obtained. Data analysis method used was the multiple regressions test with SPSS 20 tools. The results based on partial test showed that the facilities, promotions, products and locations have a significant influence on decision non muslim customers patronizing at BRIS. With a significance level under 5% or 0,05. Simultaneously, showed that the facilities, promotion, product and location have a significant influence on decision non muslim customers patronizing at BRIS. The results of the regression analysis R2 test showed that the most strongly factor affect Non Muslims customers patronizing at BRIS as a dominant influence 0,289 was promotions and also explained dependent variable at 59,3% then the remaining 41,7% can be explained by other variables which is not included in this study.